Augmenting the Tolerance Potential of Muskmelon (Cucumis melo L.) Using Salicylic Acid: Salicylic Acid Increases Salt Tolerance in Muskmelon (Biological Sciences - PJSIR, 2022)
Salicylic acid (SA) is considered an important plant hormone that controls many aspects of plant growth and development, as well as resistance to biotic and abiotic stresses. In current investigations, a pot experiment consisting of four different levels of SA (0, 1, 2 and 3 mM SA) were tested on growth and physiological attributes of muskmelon (Cucumis melo L.), grown at different salinity levels (0, 50, 100 mM NaCl). Results revealed that all the morphological and physiological attributes were significantly (P